ChemInform Abstract: Flexizyme‐Mediated Genetic Reprogramming as a Tool for Noncanonical Peptide Synthesis and Drug Discovery. Issue 35 (8th August 2013) - Passioura, Toby; Suga, Hiroaki
Abstract Review: 38 refs.